Homophobia and heterosexism : a military social work perspective - Addinall, Ronald Mark (Department of Social Development, 2018)
Homophobia and heterosexism are forms of prejudice found throughout societies the world over. Prejudice filters to all levels within a society and community. Prejudice thus finds its way into institutions, organisations, families and individuals. The existence of prejudice results in discrimination that causes a vast array of hurt. Homophobic attitudes and hetero-sexist perceptions are known to have impacted social work as a profession as well as social workers as individuals, socialised within society and communities. The same attitude and perceptions are known to be rife within the military as an institution. Prejudice and discrimination has been deemed unconstitutional. Prejudice and discrimination based on sexual orientation, the focus of this study, are prohibited by the Constitution of South Africa as well as by a policy document of the South African National Defence Force. Changes in law and policy do not necessarily reflect changes in attitudes and perceptions by those on who these policies and laws apply. Social workers with homophobic attitudes and hetero-sexist attitudes are not able to offer a professional service to homosexual clients, and could cause harm where healing is needed. In this study an explorative non-experimental field study was undertaken investigating the existence and extent of homophobic attitudes and hetero-sexist perceptions amongst military social workers employed at Military Health Units, practicing in the Western Cape Province of South Africa. The findings of the study indicate that even though the military social workers were not severely homophobic or hetero-sexist, they did reflect a significant degree of reservation. Most of the military social workers did not consider themselves equipped to offer services to homosexual clients.